Gestión del personal en el Gobierno Autónomo Descentralizado Municipal del Cantón Montalvo - Muñoz Limones, María José (2020)
This case study is carried out in the Municipal Decentralized Autonomous Government of the Montalvo canton, which is dedicated to administering the canton autonomously to the national government, through public management through the collection of property taxes, transit, operation of commercial premises and municipal taxes, aimed at citizens of the same canton in order to satisfy or solve the various concerns of people in different areas, the purpose of this research is to analyze the causes that generate inadequate personnel management, those that are related to absenteeism, working hours, teamwork, office infrastructure, among others.